Correction: Characterization of Three Novel Fatty Acid- and Retinoid-Binding Protein Genes (Ha-far-1, Ha-far-2 and Hf-far-1) from the Cereal Cyst Nematodes Heterodera avenae and H. filipjevi. - PLOS ONE Staff (PLoS ONE, 2016)
[This corrects the article DOI: 10.1371/journal.pone.0160003.].